Effectiveness of Using Whatsapp Social Media as an Organizational Communication Media - Fadhiil Dhiya' Ulhaq; Leonard Dharmawan; Enden Darjatul Ulya (IJESS International Journal of Education and Social Science, 2026)
Organizational communication is an important foundation for the sustainability and operational efficiency of an institution. This study analyzes the effectiveness of WhatsApp social media in organizational communication at the Galih Pakuan Center, a technical implementation unit for the Social Rehabilitation Assistance (ATENSI) program. This study analyzes the influence of individual characteristics on the effectiveness of organizational communication through the use of WhatsApp social media among Galih Pakuan Center employees. Using a descriptive quantitative method with a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, this study involved 58 respondents selected through a purposive sampling technique. The results showed that individual characteristics did not significantly influence the use of WhatsApp social media (path coefficient -0.151 and p-value 0.568), but significantly influenced the effectiveness of organizational communication (path coefficient 0.229 and p-value 0.036). The use of WhatsApp social media was proven to have a significant effect on the effectiveness of organizational communication (path coefficient 0.706 and p-value 0.000). The results of the mediation test indicate that WhatsApp social media use does not mediate the influence of individual characteristics on the effectiveness of organizational communication with a low mediation effect value (0.0113). This study concludes that WhatsApp use directly increases the effectiveness of organizational communication, while individual characteristics directly influence the effectiveness of organizational communication without the intermediary of WhatsApp social media use.